2018
DOI: 10.3389/fped.2018.00293
|View full text |Cite
|
Sign up to set email alerts
|

Single-Port Laparoscopic Assisted Transcrotal Orchidopexy for Palpable Inguinal Canalicular Cryptorchidism Accompany With Indirect Inguinal Hernia

Abstract: Purpose: To assess the outcomes of a novel laparoscopic assisted transcrotal orchidopexy (LATO) combined with percutaneous extraperitoneal closure (PEC) for palpable inguinal canalicular cryptorchidism accompany with indirect inguinal hernia, and evaluate its safety and efficiency.Materials and Methods: A retrospective cohort study for single-port LATO-PEC and traditional inguinal orchidopexy (TIO) was performed between 2011 and 2014. Totally 53 children with both palpable inguinal canalicular testes and indir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…If cPPV exists, ligation can be performed to close it and avoid a second surgery. The prevalence of cPPV was 45% (9/20 testes) in our LATO group, which is comparable to that reported by Ma (46.8%, 15/32 low palpable UDT) (13) and You (46.8%, 223/677 inguinal palpable UDT) (20).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…If cPPV exists, ligation can be performed to close it and avoid a second surgery. The prevalence of cPPV was 45% (9/20 testes) in our LATO group, which is comparable to that reported by Ma (46.8%, 15/32 low palpable UDT) (13) and You (46.8%, 223/677 inguinal palpable UDT) (20).…”
Section: Discussionsupporting
confidence: 88%
“…A potential bias of our study is reflected in the significantly lower PPV rate (58.1%) of our LATO approach group compared with that (100%) of the published LATO approach groups (13,14). The patency rates of PV differ according to testicular location in cryptorchidism; in particular, a distal testicular location is associated with a low patency PV rate (30).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Cuda et al reported their clinical experience that the rate of laparoscopic and scrotal orchiopexy increased, whereas the inguinal orchiopexy decreased ( 25 ). The laparoscopic technique gradually tends to have fewer incisions and even a single port, and the single practice trend is becoming more and more warrant in minimal invasive surgery ( 33 ). SISO meets the concept of being minimally invasive and the demands of patients; it is a safe, effective, promising, and potential surgical approach alternative to TTIO.…”
Section: Discussionmentioning
confidence: 99%